ESTRUTURA E PROPRIEDADES ÓPTICAS DO SISTEMA TITANATO-ESTANATO DE ESTRÔNCIO [Sr(Ti1-xSnx)O3 x = 0; 0,25; 0,50; 0,75; 1] - Inglês, Daniella (2013)
Titanates have perovskite crystalline structure very known for electrical and optical properties used in the electronic devices such as sensors, capacitors, nonvolatile and dynamic random access memories. In particular, titanates structures are characterized for the ABO3 formula being A crystallographic site formed by 12 atoms neighbors and B crystallographic site formed by 6 atoms neighbors. However, researches about strontium titanate-stannate system are found minimally in the literature. Articles discussing synthesis, characterization and compositions are insufficiently presented. This project shows a theoretical study of the structure and optical properties of the strontium titanate-stannate system for different substitutions [Sr(Ti1-xSnx)O3 x = 0; 0,25; 0,50; 0,75; 1]. It was used theoretical-computational methodology based on, Density Functional Theory (DFT) with B3LYP functional to calculate the structure of the models SrTiO3 (STO), Sr(Ti1-xSnx)O3 (STS) and SrSnO3 (SSO). Theoretical data of parameter lattice, cell unit angles, volume, band gap, overlap population, charges and free energy are presented as well as analysis and discussion of the results for band structure (EB), density of states (DOS), electron density maps. Thus, one may present the data obtained and investigate the properties of the materials.